The rise in mortality due to intentional self-poisoning by medicines in Brazil between 2003 and 2022: relationship with regional and global crises - Souza, Maximiliano Loiola Ponte; Orellana, Jesem Douglas Yamall; Jesus, Francimar Oliveira; Horta, Bernardo Lessa (Frontiers in Public Health, 2024)
In recent years, suicide rates in Brazil have increased, but little is known about the temporal behavior and characteristics of suicides due to intentional self-poisoning by medicines. The aim of the present study was to provide an overview of Evaluate the sociodemographic characteristics and place of death related to suicide due to intentional self-poisoning by medicines and, to evaluate the trends of mortality rates in Brazil between 2003 and 2022, and its relationship with regional and global crises. Ecological time series study with data from the Mortality Information System of the Brazilian Ministry of Health, related to individuals aged 10 years and over, who committed suicides due to intentional drug overdose, in the period from 2003 to 2022. The analyses were performed in the R environment in RStudio. Between 2003 and 2022, there was a predominance of deaths in women (55.5%), individuals aged 30-49 years (47.2%), of white race/color (53.2%), occurring in health facilities (67.0%), using drugs or unspecified substances (40.4%); a higher concentration in the southern region (22.8%) and a positive trend in mortality rates due to intentional drug overdose, especially from 2016 onwards. A rise of 264% was observed in the comparison of 2022 and 2003. A peculiar sociodemographic profile was observed in the victims of intentional selfpoisoning by medicines and a positive temporal trend in mortality rates, especially in a period marked by regional and global crises.